Family Support, Family Incarceration, and Substance Use Among Adjudicated Youth Across Time - Kopf, Samantha (American journal of criminal justice, 2024)
Substance use remains an all-too-common experience for youth and young adults involved in the U.S. juvenile and criminal justice system. Compounding this effect, adjudicated youth are likely to have family members also involved in the criminal justice system. While family support has long been cited as a protective factor against youthful substance use, family criminal justice contact may interrupt this relationship and exacerbate substance use issues for youth as they age. Using eleven waves of data from the Pathways to Desistance dataset, we examine the independent and interdependent influences of family support and family criminal justice contact on substance use as youth move into young adulthood. Results from a series of cross-lagged dynamic panel models demonstrate that after accounting for baseline levels of substance use, family support does not significantly relate to substance use across time. Family criminal justice contact, however, relates to significant increases in substance use.